Fast Neuro: A Care Model to Expedite Access to Neurology Clinic. Issue 2 (April 2022) - Roy, Shuvro; Keselman, Inna; Nuwer, Marc; Reider-Demer, Melissa
Abstract : Background and Objectives: We set out to improve outpatient neurology access while reducing patient volume in the emergency department (ED) for nonemergent neurologic complaints. Methods: We created a rapid access model, University of California Los Angeles (UCLA) Fast Neuro, for patients referred from affiliated EDs to outpatient neurology, enabling appointments within 1 week of referral. Rapid access appointments were also available to established neurology patients with urgent concerns. Fast Neuro was built to reduce nonemergent neurologic care in the ED, improve outpatient neurology access, and avoid use of inpatient neurology services for nonemergent consults. The volume of referrals and neurology consults from the ED and wait time from referral to appointment were measured. Surveys were conducted at 3 and 6 months to assess satisfaction with the model by all stakeholders. Results: From January 2019 through January 2021, 201 patients were referred to outpatient neurology through UCLA Fast Neuro. Wait time for an outpatient neurology appointment was reduced from the prior period by 82.5% (7.0 ± 5.5 vs 40 ± 4.1 days). The number of nonemergent consults from the ED was reduced by 60% (4.1 ± 1.9/mo vs 10.3 ± 1.7/mo). Surveys showed wide acceptance of the new model with 92% of attending physicians and advanced practice providers and 89% of residents endorsing that UCLA Fast Neuro patients did not detract from their clinic experience. Discussion: UCLA Fast Neuro improved ED throughput, reduced inpatient neurology consults from the ED, and decreased wait times for outpatient neurology appointments without using the inpatient neurology service for nonurgent consults. UCLA Fast Neuro was successful. Exploration of how to scale and implement the model of access more broadly is warranted.